Potential cellular endocrinology mechanisms underlying the effects of Chinese herbal medicine therapy on asthma - Meng, Zeyu; Chen, Huize; Deng, Chujun; Meng, Shengxi (Frontiers in Endocrinology, 2022)
Asthma is a complex syndrome with polygenetic tendency and multiple phenotypes, which has variable expiratory airflow limitation and respiratory symptoms that vary over time and in intensity. In recent years, continuous industrial development has seriously impacted the climate and air quality at a global scale. It has been verified that climate change can induce asthma in predisposed individuals and that atmospheric pollution can exacerbate asthma severity. At present, a subset of patients is resistant to the drug therapy for asthma. Hence, it is urgent to find new ideas for asthma prevention and treatment. In this review, we discuss the prescription, composition, formulation, and mechanism of traditional Chinese medicine monomer, traditional Chinese medicine monomer complex, single herbs, and traditional Chinese patent medicine in the treatment of asthma. We also discuss the effects of Chinese herbal medicine on asthma from the perspective of cellular endocrinology in the past decade, emphasizing on the roles as intracellular and extracellular messengers of three substances—hormones, substances secreted by pulmonary neuroendocrine cells, and neuroendocrine-related signaling protein—which provide the theoretical basis for clinical application and new drug development.